Pozzolanic Behavior of Mt. Pinatubo Ejecta Under Natural and Accelerated Curing Condition - Jorillo Jr., Pablo A.; Verdejo, Benjamin D. (Philippine Engineering Journal, 2021)
This paper describes the results of the study on the evaluation of the pozzolanic behavior of Mt. Pinatubo ejecta under natural and accelerated curing conditions. The study is essentially a developmental research aimed in providing a comprehensive characterization of the volcanic ejecta in comparison with the local fly-ash. Two types of accelerated curing were examined viz., high pressure steam curing and boiling-cooling method. Various types of ejecta materials and percentage cement replacements were investigated to determine the optimum type and proportion in a cement based mortar matrix based on the criteria of strength and dimension stability.